2022
DOI: 10.3389/fmed.2022.852973
|View full text |Cite
|
Sign up to set email alerts
|

mTOR Inhibitor Use Is Associated With a Favorable Outcome of COVID-19 in Patients of Kidney Transplant: Results of a Retrospective Study

Abstract: IntroductionIn solid organ transplant recipients, COVID-19 is associated with a poor prognosis because of immunosuppression. Some studies suggest a potential therapeutic role of mammalian Target of Rapamycin (mTOR) inhibitors in SARS-CoV-2 infection. This study aimed to assess the impact of mTOR employment on the evolution and outcome of SARS-CoV-2 infection in solid organ transplant recipients.MethodsWe enrolled kidney transplant patients attending the Azienda Ospedaliera Universitaria Federico II in Naples a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
2
3
0
Order By: Relevance
“…Nevertheless, this beneficial effect of mTORi after two doses of vaccine was no maintained in the adjusted model in our cohort, findings also noted by Bae (33). Several authors found similar results with MPA and mTORi in different groups of patients who received two doses (33)(34)(35)(36)(37), even proposing the temporary suspension of treatment during the vaccination process (38). But we go further and performed an analysis of immune response after the third or booster dose and different results were observed.…”
Section: Discussionsupporting
confidence: 56%
“…Nevertheless, this beneficial effect of mTORi after two doses of vaccine was no maintained in the adjusted model in our cohort, findings also noted by Bae (33). Several authors found similar results with MPA and mTORi in different groups of patients who received two doses (33)(34)(35)(36)(37), even proposing the temporary suspension of treatment during the vaccination process (38). But we go further and performed an analysis of immune response after the third or booster dose and different results were observed.…”
Section: Discussionsupporting
confidence: 56%
“…The finding of the favorable impact of mTOR inhibitors confirmed what was reported by Heldman et al ( 22 ) and what reported from our previous experience, in which the patients who received mTOR inhibitors, as part of their immunosuppressive therapy, compared to other regimens had a lower chance of developing a moderate or severe form of the disease [OR = 0.8, 95, CI: (0.21–0.92), p = 0.041] ( 36 ). However, our own data are not in agreement to what has been reported by Genuardi et al ( 37 ).…”
Section: Discussionsupporting
confidence: 89%
“…12 The optimal management of transplant immunosuppression during COVID-19 is unclear. We stopped MMF and later introduced a mTOR inhibitor, as these have been associated with less and more favourable outcomes, respectively, in KT recipients with COVID-19, 13,14 despite the potential for everolimus to cause pulmonary toxicity. 15 F I G U R E 3 Whole genome sequencing analysis of seven samples collected between week 4 and 18 post initial infection.…”
Section: Discussionmentioning
confidence: 99%